Exploring English in an EMI nursing program: Native English varieties, ELF, and translingual practices - Komilie Situmorang; Santa Maya Pramusita (Universitas Syiah Kuala, 2025)
English Medium Instruction (EMI) has been implemented globally as a strategy for the internationalization of Higher Education Institutions to promote global competence and mobility. However, the concept of English within the EMI context has been scrutinized, as studies reveal that the definition of English in EMI is often contextual. This shift has brought English as a Lingua Franca (ELF) into focus. Given the limited research in Indonesia exploring EMI through the perspectives of ELF and translingual practices, this study examines these concepts within the context of the nursing EMI program. The study draws on a rich dataset, using in-depth interviews with international nursing students to analyze the conceptualization of English, ELF, and translingual practices. Findings reveal a disparity between students preconceived notions and actual practices. Students commonly perceive English in EMI as a native variety shaped by exposure to popular culture such as movies, songs, and social media. However, ELF practices emerge as essential strategies for achieving effective communication, emphasizing adaptability and mutual understanding. Translingual practices manifest in the form of gado-gado Englisha blend of languageswhich is seen as a creative and dynamic linguistic choice but also criticized as being less proficient or standardized. This study highlights the complexities of EMI implementation and advocates for a dynamic and flexible approach to navigating multilingual classroom contexts.